Eksistensi Perempuan Madura Dalam Pembangunan Daerah Berbasis Berkelanjutan (Sdgs) Di Sektor Pariwisata Terhadap Pertumbuhan UMKM - Ibnullah, Moh Imam; Hayati, Nur; Musyarofah, Siti; Djasuli, M (Akuisisi : Jurnal Akuntansi, 2024)
This study aims to see how the involvement and role of Madurese women in sustainable regional development (SDGs) in the tourism sector of Sumenep Regency, namely Lombang Beach, Slopeng Beach and the Keraton Museum on the growth of MSMEs and PAD. Where many studies show that there is gender inequality that occurs in various sectors including the tourism sector which is actually contrary to the fifth goal of the SDGs, namely gender equality. This study uses a qualitative method with a case study approach and uses interviews and observations as data collection techniques. This study identifies the role or involvement of Madurese women divided into 4, namely 1) women at the management level, 2) women at the service/facility level 3) women at the promotion level 4) women at the MSME business unit manager level.